2017
DOI: 10.1371/journal.pone.0184590
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the STK4/Hippo signaling network in prostate cancer cell

Abstract: Dysregulation of MST1/STK4, a key kinase component of the Hippo-YAP pathway, is linked to the etiology of many cancers with poor prognosis. However, how STK4 restricts the emergence of aggressive cancer remains elusive. Here, we investigated the effects of STK4, primarily localized in the cytoplasm, lipid raft, and nucleus, on cell growth and gene expression in aggressive prostate cancer. We demonstrated that lipid raft and nuclear STK4 had superior suppressive effects on cell growth in vitro and in vivo compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
1
22
0
1
Order By: Relevance
“…Co-expression analysis indicated that circRNAs were closely correlated with certain mRNAs, some of which were reported to play vital roles in PCa, such as ZNF217 and STK4 [28,29]. Conceivably, circRNAs might influence PCa carcinogenesis via these mRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…Co-expression analysis indicated that circRNAs were closely correlated with certain mRNAs, some of which were reported to play vital roles in PCa, such as ZNF217 and STK4 [28,29]. Conceivably, circRNAs might influence PCa carcinogenesis via these mRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…8,9 In addition, existing literature has suggested that DNA hypermethylation and post-translational modification can mediate the loss of STK4 activity. 11 The Hippo signalling pathway, comprised of mammalian STE20-like protein kinase 1 and 2 (MST1/2), large tumour suppressor kinase 1/2 (LAST1/2) and its downstream transcription co-activator, Yesassociated protein (YAP), have been implicated in the regulation of tumour suppression concerning tissue repair and regeneration. 11 The Hippo signalling pathway, comprised of mammalian STE20-like protein kinase 1 and 2 (MST1/2), large tumour suppressor kinase 1/2 (LAST1/2) and its downstream transcription co-activator, Yesassociated protein (YAP), have been implicated in the regulation of tumour suppression concerning tissue repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ready et al concluded that the dysregulation of STK4 is linked to carcinogenesis associated with poor outcomes in addition to implicating the Hippo signalling pathway in this process. 11 The Hippo signalling pathway, comprised of mammalian STE20-like protein kinase 1 and 2 (MST1/2), large tumour suppressor kinase 1/2 (LAST1/2) and its downstream transcription co-activator, Yesassociated protein (YAP), have been implicated in the regulation of tumour suppression concerning tissue repair and regeneration. 12 Based on the exploration of the aforementioned literature, we asserted the hypothesis that lncRNA TNRC6C-AS1 could potentially work in tandem with STK4 and the Hippo signalling pathway in TC cells, whereby tumour progression can be regulated.…”
Section: Introductionmentioning
confidence: 99%
“…22 A study has showed that the protein level of STK4 decreases in the progression of prostate cancer. 23 Based on RIP assay in this study, the expression of STK4 was regulated by lncRNA TNRC6C-AS1. LncRNA TNRC6C-AS1 promoted STK4 by inhibiting the methylation of STK4 promoter, thus inhibiting the phosphorylation level of YAP and Hippo signalling pathway.…”
Section: Discussionmentioning
confidence: 76%